1996
DOI: 10.1016/s0896-6273(00)80140-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant BDNF Rescues Deficits in Basal Synaptic Transmission and Hippocampal LTP in BDNF Knockout Mice

Abstract: Brain-derived neurotrophic factor (BDNF) is expressed at high levels in hippocampal neurons, and its expression is modulated by neural activity. Knockout mice can be used to study the roles of molecules like BDNF in synaptic plasticity with more molecular specificity than is possible using pharmacological approaches. Because in conventional knockouts the disrupted gene product is absent in all tissues throughout the life of the animal, developmental effects may complicate the interpretation of deficits in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
792
1
5

Year Published

1999
1999
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,138 publications
(832 citation statements)
references
References 49 publications
34
792
1
5
Order By: Relevance
“…Collagen I and fibronectin may be involved in hMSC-induced functional improvement. At 6 weeks postgrafting, the latest time point of the present study, the grafted MSCs still maintained their primitive properties producing collagen I and fibronectin (41,44). Numerous studies have shown that extracellular matrix (ECM) proteins influence cell proliferation, migration, survival, and differentiation (20,21,46,58).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Collagen I and fibronectin may be involved in hMSC-induced functional improvement. At 6 weeks postgrafting, the latest time point of the present study, the grafted MSCs still maintained their primitive properties producing collagen I and fibronectin (41,44). Numerous studies have shown that extracellular matrix (ECM) proteins influence cell proliferation, migration, survival, and differentiation (20,21,46,58).…”
Section: Discussionmentioning
confidence: 50%
“…Numerous studies suggest that neurotrophic factors play important roles in brain plasticity. Neurotrophic factors can enhance neuronal sprouting (11), synaptogenesis (18), long-term potentiation (2,30,41), and neurotransmission (25) and increase neurotransmitter release (26,27,34). Humpel et al reported that human fetal cortical grafts expressed nerve growth factor, brain-derived neurotrophic factor, and neurotrophin-3 mRNA after transplantation to cortical cavities in rats (23).…”
Section: Discussionmentioning
confidence: 99%
“…Also of possible pertinence to such clinical neuropsychiatric disorders, BDNF has been shown to be essential to long-term potentiation (LTP), a cellular process proposed to underly learning and memory (Patterson et al 1996). Consistent with a role for BDNF in learning, rats pre-treated with anti-BDNF antibodies show impairments in spatial learning and memory (Mu et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that stressinduced decreases in hippocampal BDNF levels may underly disturbances in memory and cognition common to several disorders that may otherwise vary in their etiology and symptom profiles (Wolfe and Schlesinger 1997;Yousef et al 1998). Also of possible pertinence to such clinical neuropsychiatric disorders, BDNF has been shown to be essential to long-term potentiation (LTP), a cellular process proposed to underly learning and memory (Patterson et al 1996). Consistent with a role for BDNF in learning, rats pre-treated with anti-BDNF antibodies show impairments in spatial learning and memory (Mu et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation